El proceso contable y su incidencia en la administración financiera de la Escuela Sindicato de Choferes Profesionales San Miguel, periodo 2017 - Arguello Estrada, Diana Jaqueline (2018)
The Union School of Professional Drivers San Miguel provides professional training services to the community of the province and the country, eagerly seeks to constantly improve its positioning and competitiveness for the world in the market and overcome financial doubts that it faces, reason why which is essential to have an adequate accounting process that allows you to carry out your transactions based on legal and current accounting principles and rules. In the development of this research qualitative and quantitative methodology was used, which allowed to collect and analyze specific data on accounting and financial information on the basis of economic activities and culture of the school, was examined through the application of methods, techniques and instruments to gather reliable information, since the work is based on the accounting process and financial administration, variables that served to diagnose the current situation. A proposal was proposed with basic elements such as the change of the current accounting process, the financial management through the necessary financial direction to contribute to the decision making and the optimization of the economic resources, the general proposal in a reformed process. of the school, that provides true financial data and an adequate administration, based on effective accounting information. When talking about a process, the set of steps, techniques and activities that must be followed are established, so that a process is based on theoretical and scientific bases supported by bibliography according to the subject of study; Then, this financial accounting structure can be facilitated according to your needs and activities, so that the economic resources are correctly allocated by the administration. KEY WORDS: Accounting Process, Accounting, Financial Administration, Financial Statements, Financial Reasons.